(Invited) Development of SiGeSn Technique Towards Mid-Infrared Devices in Silicon Photonics. (18th August 2016) - Du, Wei; Al-Kabi, S.; Ghetmiri, Seyed; Tran, Huong; Pham, Thach; Alharthi, Bader; Mosleh, Aboozar; Margetis, Joe; Tolle, John; Naseem, Hameed A; Mortazavi, Mansour; Sun, Greg; et al.
Abstract : SiGeSn techniques are of great interest in the area of Si photonics mainly due to the compatibility with current Si complementary metal-oxide semiconductor (CMOS) process and the tunable bandgap allowing the optoelectronic devices operation features broad wavelength coverage in near- and mid-infrared ranges. Moreover, the independent engineering of bandgap energy and lattice constant enables the design of SiGeSn-based device to be more flexible. In this work, the following aspects regarding the SiGeSn techniques are investigated: 1) low-defect material growth technique via Chemical Vapor Deposition (CVD) system; 2) advanced material and optical characterizations of SiGeSn alloys; 3) demonstration of SiGeSn-based photoconductors.